NICK DUNNE’S DISLOYALTY IN GILLIAN FLYNN'S GONE GIRL - Darma, Difky Arung; Andayani, Ambar (TANDA, 2024)
This study discusses about Nick Dunne’s disloyalty in Gillian Flynn's Gone Girl. In analysing the data from Dunne’s character, this study applies descriptive qualitative method and psychological theory which is aimed to explain the portrayal, causes, and effects of Nick Dunne’s disloyalty. There are three categories of the findings as the result of this study, the type of Dunne’s disloyalty, the causes of Dunne’s disloyalty and the effects of Dunne’s disloyalty. The type of Dunne’s disloyalty is romantic love affair. The causes of Dunne’s disloyalty are desire of novelty, poor communication, insecurity, and lack of intimacy. There are two kinds of effects from Dunne’s disloyalty, namely effect on the doer and effect on the victim. The effects of Dunne’s disloyalty on the doer, Dunne himself, include suffering from guilt and shame, inner conflict, identity crisis, self-doubt, fear of repercussion, desire of personal growth and change, and lack of intimacy with his wife. The effects of Dunne’s disloyalty on the victim, Amy, include anguish from betrayal and emotional trauma, loss of self-esteem, trust issues, emotional roller coaster, self-blame, fear of repeating betrayal, and lack of intimacy.